Visibility intervention of circulation path configuration of Alun-alun Merdeka Malang City as Covid-19 resilient space - Triska Prakasa Wikananda; Nedyomukti Imam Syafii (ARTEKS : Jurnal Teknik Arsitektur, 2022)
With the lack of clarity on when the Covid-19 pandemic will end, there is a demand for a new design approach to the configuration of circulation paths in public open spaces. a design approach that can break up the crowd and form a space with a low-density pattern can be a new form of adaptation to new social arrangements and conditions after the pandemic. Therefore, it is necessary to conduct research through simulations related to the spatial aspects of the configuration of public open spaces and the activities in them, to see how the form of space and the elements supporting activities in accommodating activities, and predicting what forms of intervention are appropriate in accommodating activities in the new normal period. This study uses an experimental-simulative method through simulation of space syntax on the circulation path through the DephtmapX 0.50, to identify opportunities for regeneration of new designs to respond to the spatial potential of existing urban areas. It can be seen from the results of the space syntax simulation that with the addition of activity spaces and new circulation paths with strong symmetry, it can form a more even distribution of visitors to all parts of public open spaces.